1950
DOI: 10.1149/1.2777899
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetics of the Reactions of Beryllium with Oxygen and Nitrogen and the Effect of Oxide and Nitride Films on its Vapor Pressure

Abstract: A systematic study of the reaction of beryllium with oxygen is made over the temperature range of 350 ~ to 950~ The experimental data may be fitted by the parabolic rate law except for the initial period of the reaction. A plot of log K/T vs. 1/T gives an energy of activation of 50,300 calories per mole. A comparison of this rate data with other metals and alloys shows that vacuum-treated beryllium has the smallest parabolic reaction rate constant at 900~ of any metal or alloy that we have studied.The reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1960
1960
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(15 citation statements)
references
References 20 publications
(44 reference statements)
2
13
0
Order By: Relevance
“…8 @ 1,500 8C and 1-atm O 2 , >50% of the specimen oxidized within 15 min [weight/size of specimen not given]. 21 At the bp of beryllium, oxidation is rapid and the oxide forms a porous coat (corroborates characteristics of oxide depend on temperature during formation) and airborne release depends on the degree of mechanical disruption by external action. 23 At temperatures >mp oxide ($2,547 8C), the oxide layer is severely disrupted and berylliumvapors condense to d G 1-mm particles in the vapor state .…”
Section: Oxidation -Experimental Observations (Literature Review)mentioning
confidence: 99%
See 3 more Smart Citations
“…8 @ 1,500 8C and 1-atm O 2 , >50% of the specimen oxidized within 15 min [weight/size of specimen not given]. 21 At the bp of beryllium, oxidation is rapid and the oxide forms a porous coat (corroborates characteristics of oxide depend on temperature during formation) and airborne release depends on the degree of mechanical disruption by external action. 23 At temperatures >mp oxide ($2,547 8C), the oxide layer is severely disrupted and berylliumvapors condense to d G 1-mm particles in the vapor state .…”
Section: Oxidation -Experimental Observations (Literature Review)mentioning
confidence: 99%
“…Experimental results have shown that the oxidation of beryllium is controlled by the release of beryllium vapor through the ''blue oxide'' layer. 15,[19][20][21]23 The airborne release of significant amounts of the beryllium oxide is primarily concerned with the potential conditions that may result in accelerated oxidation and ignition of the beryllium handled and processed within non-reactor, nuclear facilities. The oxidation process is affected by many parameters that may increase the rate of beryllium metal vapor.…”
Section: Oxidation Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Gulbransen and Andrew [ 11 ] have examined the kinetics of Be oxidation by measuring the weight gain during heating in oxygen with a vacuum microbalance. They observed that at constant temperature the oxidation rate follows a parabolic time dependence indicating that diffusion of Be through the oxide is the rate determining process.…”
Section: Introductionmentioning
confidence: 99%